Endocrine Profile and Reproductive Performance in Heifers Induced to Lactation - Luz, Gabriela Bueno; Maffi, Andressa Stein; Xavier, Eduardo Gularte; Correa, Marcio Nunes; Gasperin, Bernardo Garziera; Brauner, Cassio Cassal (Acta Scientiae Veterinariae, 2019)
Background: Low reproductive efficiency has been one of the main factors that lead to dairy herd culling in the reproductive age. In multiparous animals, such inefficiency and culling can occur because of various factors and may be associated with occasional endocrine failures. To avoid revenue losses that incur due to lack of lactation, lactation is artificially induced in the animals that are not pregnant, using a defined protocol. The aim of this study was, therefore, to evaluate and compare the reproductive performance of heifers submitted to the induction protocol with that of pregnant heifers during the transition period. Materials, Methods & Results: Sixty Holstein heifers, 32 ± 0.6 months of age, were divided into two groups: Control Group (Control, n = 30) comprising pregnant heifers that were accompanied since 21 days before the expected calving date until 224 days in milk (DIM) and an Induction Group (Induction, n = 30) comprising non-pregnant heifers submitted to a lactation induction protocol, accompanied from the beginning of the protocol until 224 DIM. For evaluation of the endocrine profile (progesterone and estradiol concentrations) of these animals, blood samples were collected at two periods: the pre-lactation (weeks -3, -2 and -1) and post-lactation (weeks 1 and 4). Heifers from both groups were submitted to weekly reproductive evaluations, from the beginning of lactation until 35 DIM. Uterine examinations were performed using ultrasonography and vaginoscopy to evaluate uterine content, cervical opening, and mucosal aspect. Females in good reproductive health were subjected to a hormonal protocol for timed artificial insemination (TAI). The pregnancy rate of heifers that could reproduce (Control, n = 13, and Induction, n = 20) were evaluated and inseminated until 49 DIM. Progesterone levels were similar (P > 0.05) in the two groups at both pre- and post-start of lactation. Estradiol concentrations were different (P < 0.01) among groups only in the pre-lactation period. Higher levels of progesterone (P = 0.06) were observed in the induced heifers (Induction Group = 1.07 ± 0.23 ng/mL and Control Group = 0.38 ± 0.28 ng/mL). Therefore, in the fourth week, induced heifers exhibited higher luteinic activity, the progesterone concentration was above 1 ng/mL in 42% of the animals, while just 12.5% of the Control heifers had it. The overall pregnancy rate was 47.75%. The pregnancy rate recorded for induced heifers and Control heifers was 40% and 55.55%, respectively. Discussion: Progesterone and estradiol evaluations were performed in the first week after the beginning of the lactation to evaluate the metabolism and physiological concentration of the hormones used during the protocol. The measurements were again performed in the fourth week to evaluate the return to cyclicity of the heifers in both groups. The high serum concentrations of estradiol attained during the induction, in the pre-lactation period, may have possible interfered with the uterine environment and follicular population of these animals. Furthermore, it is possible that the hormonal combination used has a central effect on the synthesis and release of gonadotrophins and/or an effect on the ovarian follicular population. Based on the hormonal profile evaluated, particularly the endocrine profile, and the reproductive performance of heifers, the results suggest that the protocol for induced lactation has a positive effect on fertility.